Effects of seasonal temperature regimes on embryo growth and endogenous hormones of Taxus chinensis var. mairei seeds - Zhou, Man; Xu, Yan; Wang, Fang; Yang, Xuejun; Lu, Shunbao; Zhang, Yanjie (Frontiers in Plant Science, 2023)
Seed dormancy is a mechanism that prevents seeds from germinating at times of the year when conditions are unfavorable, that is, when the chance of seed survival is low. Determining the seasonal dynamics of seed dormancy is important for exploring how plant regeneration is adapted to the environment. We studied the seed dormancy status of Taxus chinensis var. mairei, an endangered species in China, under simulated seasonal temperature regimes. The embryo length, embryo-to-seed (E : S) ratio, and percentage of seeds with a split seed coat increased when seeds were stratified at spring and autumn temperature regimes. The abscisic acid (ABA) content decreased during stratification at simulated seasonal temperatures, but no obvious pattern in the content of gibberellic acid (GA) and indole acetic acid (IAA) was observed. The GA–ABA and IAA–ABA ratios increased during stratification. These results suggest that T. chinensis var. mairei seeds have morphophysiological dormancy, and that the seasonal dynamics of seed dormancy break are controlled by endogenous hormones and their balances, which was confirmed by the results of a field experiment. Our study provides useful information for understanding the natural population regeneration and propagation of this threatened species.